2019
DOI: 10.21203/rs.2.16986/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification and analysis of KLF13 variants in patients with congenital heart disease

Abstract: Background: The protein Kruppel-like factor 13 (KLF13) is a member of the KLF family that has been identified as a novel cardiac transcription factor which is involved in heart development. However, the relationship between KLF13 variants and CHDs in humans remains largely unknown. The present study aimed to screen the KLF13 variants in CHDs patients and genetically analyze the function of these variants. Methods: KLF13 variants were sequenced in a cohort of 309 CHD patients and population-matched healthy cont… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…As one member of the KLF family, the KLF13 protein harbors four critical structural domains encompassing a transactivation domain, which functions to transactivate downstream target genes, a transcriptional inhibition domain, which serves to transcriptionally inhibit downstream target genes, a nuclear localization signals responsible for nuclear localization, and three zinc-fingers required for binding to target gene promoters and interaction with other transcriptionally cooperative partners (67,87). Previous investigations have substantiated the ample expression of KLF13 in the hearts of both humans and vertebrates during embryonic development, and the pivotal effect of KLF13 on cardiovascular morphogenesis (66,67,86,88). Recent experimental studies have corroborated that KLF13 transactivates the expression of several downstream genes, encompassing NPPA, NPPB, VEGFA and ACTC1, separately or synergistically with TBX5, GATA4 and GATA6 (86,88).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As one member of the KLF family, the KLF13 protein harbors four critical structural domains encompassing a transactivation domain, which functions to transactivate downstream target genes, a transcriptional inhibition domain, which serves to transcriptionally inhibit downstream target genes, a nuclear localization signals responsible for nuclear localization, and three zinc-fingers required for binding to target gene promoters and interaction with other transcriptionally cooperative partners (67,87). Previous investigations have substantiated the ample expression of KLF13 in the hearts of both humans and vertebrates during embryonic development, and the pivotal effect of KLF13 on cardiovascular morphogenesis (66,67,86,88). Recent experimental studies have corroborated that KLF13 transactivates the expression of several downstream genes, encompassing NPPA, NPPB, VEGFA and ACTC1, separately or synergistically with TBX5, GATA4 and GATA6 (86,88).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, KLF13 variations have been reported to cause distinct types of congenital cardiovascular deformities in humans, including TGA, TVA, DORV, VSD and ASD (66,67). In the present study, the affected family members who carried an identified KLF13 mutation manifested PDA, BAV and VSD, therefore expanding the phenotypic spectrum ascribed to mutant KLF13 and highlighting the genetic heterogeneity of CHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, S156N had a significantly increased ability to interact with TBX5. Although, authors suggest that the overexpression of KLF-13 associated to S156N might be accompanied by higher protein instability, resulting in a loss-of function phenotype [85] Lavallée et al, have previously described similar results, identifying Klf-13 as a modifier of Gata4, a key transcription factor for the cardiac natriuretic peptide genes Nppa and Nppb. In this study, Klf-13 Knockdown resulted in atrial septal defects, hypotrabeculation and hypoplastic myocardium in Xenopus embryos [31].…”
Section: Klfs In Congenital Heart Diseasesmentioning
confidence: 91%